Physical condition improvement in elite volleyball players - Malikov, N.; Маліков, Н.; Konoh, A.; Конох, А.; Korobeynikov, G.; Коробейников, Г.; Korobeynikova, L.; Коробейникова, Л.; Dudnyk, O.; Дудник, О.; Ivashchenko, E.; Іващенко, О. (My University, 2020)
The aim of the work – to substantiate scientifically the content of the program of planning training sessions and increase the level of functional and special physical condition of elite volleyballers. Material: The pedagogical study was attended by 14 elite female athletes specializing in volleyball. The study recorded indicators of functional and special physical condition. Results: The use of the proposed training program in the training process contributed to maintaining during the competitive period the optimal level of functional and special physical condition of female athletes: a significant (p<0,001) decrease in their indicators by the end of the competitive period was only 3-15%, while using the traditional program was significantly higher (5-50%). After the competition period, all indicators of the athletes' special physical preparedness were in line with the average level. The level of functional preparedness of the surveyed female athletes at the end of the competition period was significantly (p<0,001) reduced and considered as below average. Conclusions: While designing new programs for constructing a training process for elite athletes, it is necessary to take into account the dynamics of functional and special condition in individual microcycles, the nature of the correlation between the level of functional condition and its individual components, indicators of special physical preparedness and organization on the basis of this that enables purposeful management of the training process. It was determined that the use of volleyball players in the training process of our training program, which provided for the presence of competitive and corrective modules, dependence of their content on the results of pre-testing contributed to the maintenance of the optimal level of indicators of functional and special physical condition of female athletes throughout the competitive period. Мета роботи - обґрунтувати науково зміст програми планування навчальних занять та збільшити рівень функціонального та особливого фізичного стану елітних волейболістів. Матеріал: В педагогічному дослідженні участь взяли 14 елітних спортсменок, що спеціалізуються на волейболі. У ході дослідження зафіксовано показники функціональної та особливий фізичний стан. Результати: Використання запропонованої навчальної програми у навчальному процесі сприяло для підтримки протягом змагального періоду оптимального рівня функціонального та особливого фізичного стану спортсменки: суттєве (р <0,001) зниження їх показників лише до кінця змагального періоду 3-15%, тоді як використання традиційної програми було значно вищим (5-50%). Після змагального періоду всі показники особливої фізичної підготовленості спортсменів відповідали середньому рівню. Рівень функціональна підготовленість обстежених спортсменок на кінець змагального періоду була суттєвою (p <0,001) зменшено і вважається нижче середнього. Висновки: При розробці нових програм тренувального процесу для елітних спортсменів, необхідно враховувати динаміку функціональних можливостей та особливий стан в окремих мікроциклах, характер кореляції між рівнем функціональних стан та окремі його компоненти, показники особливої фізичної підготовленості та організації на основі цього - цілеспрямоване управління навчальним процесом. Було встановлено, що використання волейболістів у тренувальному процесі нашої тренувальної програми, яка передбачала наявність змагальних коригувальних модулів, залежність їх змісту від результатів попереднього тестування сприяла технічному обслуговуванню оптимального рівня показників функціонального та особливого фізичного стану спортсменки на всьому протязі змагального періоду.
Поліпшення фізичного стану у елітних волейболістів
Keywords: elite athletes; елітні спортсмени; physical fitness; фізична підготовка; volleyball; волейбол